An efficient IAA and BAP-assisted in vitro micropropagation through shoot tip culture of Bacopa Monnieri (L.) Wettst. – A medicinally important plant - RAJENDRA PRASAD B,; VENKATESHWARLU. M,; ODELU G,; MADAN MOHAN.G,; BABU RAO.M, (International Journal of Pharma and Bio Sciences, 2018)
A rapid, simple and efficient protocol for in vitro multiple shoot induction and plantlet regeneration was achieved from shoot tip explants of Bacopa monnieri (L.) Wettst. For this, the effect of three different cytokines on in vitro micropropagation from shoot tip explants was studied in B. monnieri. The cytokinins used were 6-benzylaminopurine (BAP), Kinetin (KN) and Thidiazuron (TDZ). They were used either individually or in combination with Indole acetic acid (IAA). Although organogenesis could be obtained on medium supplemented with BAP/KN/TDZ, the regenerated shoots failed to elongate on the same medium and showed an albino phenotype. BAP stimulated shoot regeneration and this effect was significantly enhanced when combined with IAA. BAP (3.0 mg/L) in combination with IAA (0.5 mg/L) proved to be optimal for induction maximum number of shoots from shoot tip explants within three weeks of culture. The highest number of shoots (24.0 ± 0.04) was achieved on MS medium augmented with IAA (0.5 mg/L) + (3.0 mg/L) BAP. The medium supplemented with IAA (0.5 mg/L) + (3.0 mg/L) BAP better than all other media concentrations in shoot tip explants. Individual shoots were aseptically excised and sub cultured in the same media for shoot elongation. The elongated shoots were transferred to Indole Butyric Acid (IBA) (0.5-1.0 mg/L) and Indole Acetic Acid (IAA) (0.5-1.0 mg/L) for root induction. Rooting was observed within two weeks of culture. MS medium supplemented with (1.0 mg/L) IBA proved better with seventy percent rooting after 25 days of implantation. Most of the roots were long and healthy. Rooted plantlets were successfully hardened under culture conditions and subsequently established in the field conditions. The recorded survival rate of the plants was 76.3%. Plants looked healthy with no visually detectable phenotypic variations. The plantlets (10-12 weeks old) were successfully acclimatized in soils with 85% survival frequency.